2022
DOI: 10.3390/molecules27134011
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Electronic, Reactivity, and Conformational Features of 2,5,5-Trimethyl-1,3,2-diheterophosphinane-2-sulfide, and Its Derivatives: DFT, MEP, and NBO Calculations

Abstract: In this study, we used density functional theory (DFT) and natural bond orbital (NBO) analysis to determine the structural, electronic, reactivity, and conformational features of 2,5,5-trimethyl-1,3,2-di-heteroatom (X) phosphinane-2-sulfide derivatives (X = O (compound 1), S (compound 2), and Se (compound 3)). We discovered that the features improve dramatically at 6-31G** and B3LYP/6-311+G** levels. The level of theory for the molecular structure was optimized first, followed by the frontier molecular orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Therefore, gaining precise knowledge about the conformational aspects of a molecule becomes crucial. Conformational analysis not only provides insights into the molecule’s structural flexibility but also allows for the identification of the relationship between conformational flexibility and reactivity. In 1995, Yamaguchi et al measured the microwave spectra of TGA and concluded therefrom that the mercapto-H group is involved in weak intramolecular hydrogen bonding, potentially allowing peripheral atoms to tunnel through low potential barriers associated with the twisting of C–S and C–C bonds . Subsequently, Caminati et al employed the free jet technique to reassign the rotational spectrum of TGA after observing significantly notable variations in the spectroscopic parameters between the two states of TGA previously reported by Yamaguchi et al In 2002, Fantoni et al conducted computational investigations utilizing various ab initio methods to analyze the conformation and S–H inversion barrier of TGA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gaining precise knowledge about the conformational aspects of a molecule becomes crucial. Conformational analysis not only provides insights into the molecule’s structural flexibility but also allows for the identification of the relationship between conformational flexibility and reactivity. In 1995, Yamaguchi et al measured the microwave spectra of TGA and concluded therefrom that the mercapto-H group is involved in weak intramolecular hydrogen bonding, potentially allowing peripheral atoms to tunnel through low potential barriers associated with the twisting of C–S and C–C bonds . Subsequently, Caminati et al employed the free jet technique to reassign the rotational spectrum of TGA after observing significantly notable variations in the spectroscopic parameters between the two states of TGA previously reported by Yamaguchi et al In 2002, Fantoni et al conducted computational investigations utilizing various ab initio methods to analyze the conformation and S–H inversion barrier of TGA.…”
Section: Introductionmentioning
confidence: 99%